Revision of the family Carabodidae (Acari, Oribatida) VII. Redefinition of the genus Malgasodes; redescription of M. curvisetus Mahunka, 2000; and complementary description of M. hungarorum Mahunka, 2010. Phylogenetic relationships between Malgasodes, Bovicarabodes, Afticarabodes, Congocepheus and Cavaecarabodes are discussed - Fernández, Néstor Alfredo (2014)
The genus Malgasodes is redefined; the type species M. curvisetus Mahunka, 2000, is redescribed by meansof studies using optic and Scanning Electron Microsopy (SEM), and a complementary description of M.hungarorum Mahunka, 2000 is included. Comparison of genera Malgasodes Mahunka, 2000, Bovicarabodes Fernandez, Theron, Rollard, 2013a, Cavaecarabodes Fernandez, Theron, Rollard, Rodriguez Castillo,2014, Afticarabodes Fernandez, Theron, Rollard, 2013b, and Congocepheus Balogh, 1958 is made. Problems concerning chaetotaxy, regressive evolution and neotrichy are explained and phylogenetic relationships between Malgasodes, Bovicarabodes, Afticarabodes, Congocepheus and Cavaecarabodes are discussed.